Factors that affect the English language teaching-learning process in Ecuadorian public high schools - Granda Miranda, Jhon Edison (2013)
This research is about the factors that affect the English Language teaching – learning process in Ecuadorian public high schools. The aim is to analyze the relevant factors concerning students, teachers, classroom, and educational institutions that affect the teaching process; which are conducted by the teachers in the public schools. Four methods were involved: class observations, teachers’ interviews, teachers’ questionnaires, and students’ questionnaire. The current research was completed in Riobamba, Chimborazo province. It took place in six schools; this research surveyed and analyzed fifteen teachers’ classes with their respective interviews and questionnaires; besides this, one student per class to fill the questionnaire as well. Quantitative analysis was applied in this research; the main sources of data collection were the interviews, the questionnaires, and the class observations, some others sources were also applied. The results of the observation and from the interpretation of questionnaires and interviews drew the conclusion that the classroom design and the number of students’ main difficulties during the teaching - learning process. Also, the public high schools teachers spoke Spanish more than English during their lessons.